Code Talkers Paid 3-Hour Tribute (Albuquerque Journal Albuquerque, New Mexico, 1982)
Special World War II Marine unit of Navajo Code Talkers and their survivors were honored at a ceremony at the University of New Mexico campus.
Newspaper article
Master list item #: 86
File location is in the New Mexico file Cabinet
Keywords: King, Bruce -- New Mexico Governor; Navajo Code Talkers; US Marines; Navajo Indians; Indian Ceremony; University of New Mexico